Unveiling the Subjective Perception of Health Information Sources: A Three-Dimensional Source Taxonomy Based on Similarity Judgements - Wedderhoff, Oliver; Chasiotis, Anita; Rosman, Tom; Mayer, Anne-Kathrin (Frontiers in Communication, 2018)
Although there is a multitude of taxonomies of health information sources, these taxonomies only partly include how information users classify these sources. The present paper complements this research by developing a taxonomy which is based on individuals’ subjective perceptions of the ‘universe’ of health information sources. In our study, nine non-redundant sources of health information were presented to N = 150 participants who rated all 36 possible combinations of source pairs regarding their perceived similarity. Results of nonmetric multidimensional scaling suggested three basic dimensions underlying the similarity ratings: “expertise” (lay vs. professional), “interaction” (interpersonal vs. impersonal), and “accessibility” (low vs. high). Thus, the wide array of health information sources can be structured by means of the new taxonomy arranging them on three dimensions. This allows researchers to classify each source and with this, to draw on common ground when interpreting the varying use of health information sources.